2010
DOI: 10.1124/dmd.110.032292
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of HKI-272 Covalent Binding to Human Serum Albumin

Abstract: ABSTRACT:The study was initiated as an observation of incomplete extraction recovery of N-(4- (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 23 publications
0
37
1
2
Order By: Relevance
“…The mean elimination half-life (t ½ ) after a 240 mg dose of neratinib with food was approximately 14 hours [61] which supports a once-daily dosing regimen. Binding studies show that neratinib binds reversibly to human serum albumin [67]. The pharmacokinetics of neratinib in Japanese patients [62] were similar to those observed in a US population [61] (Table 2).…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 56%
“…The mean elimination half-life (t ½ ) after a 240 mg dose of neratinib with food was approximately 14 hours [61] which supports a once-daily dosing regimen. Binding studies show that neratinib binds reversibly to human serum albumin [67]. The pharmacokinetics of neratinib in Japanese patients [62] were similar to those observed in a US population [61] (Table 2).…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 56%
“…Although the potential exists for allergic reactions if the drug acts like a hapten, this has not been observed in patients receiving afatinib. Covalent binding to human serum albumin has also been reported for another HER-2 tyrosine kinase inhibitor HKI-272 with a structure closely related to afatinib [19].…”
Section: Discussionmentioning
confidence: 92%
“…Covalent binding to albumin has been shown to cause incomplete extraction recovery of several highly plasma protein-bound drugs from human plasma, including thymoquinone and neratinib (HKI-271) [14, 15]. Neratinib is a potent irreversible tyrosine kinase inhibitor of the ErbB family of receptors (HER1, HER2, and HER4), which covalently binds to the cytoplasmic domain of ErbB receptors, thereby preventing downstream signaling [16].…”
Section: Resultsmentioning
confidence: 99%
“…Neratinib is a potent irreversible tyrosine kinase inhibitor of the ErbB family of receptors (HER1, HER2, and HER4), which covalently binds to the cytoplasmic domain of ErbB receptors, thereby preventing downstream signaling [16]. It has been shown that the incomplete recovery of nerotinib from human plasma after exhaustive extraction with organic solvent was caused by the covalent binding of the drug to the lysine residue (Lys190) of HSA via Michael addition [15]. Lys190 is located at the junction of domains I (1–188) and II (189–385) of HSA, a high-affinity region for substrate protein binding [17, 18].…”
Section: Resultsmentioning
confidence: 99%